State of the art and challenges in the environmental labelling for animal food products - Riccardo Primi; Giampiero Grossi; Pier Paolo Danieli; Andrea Vitali; Nicola Lacetera; Bruno Ronchi (Italian Journal of Animal Science)
In the latter half of the twentieth century, particularly in developed countries, a growing awareness of the environmental impact of personal choices—encompassing climate, pollution, land degradation, and biodiversity loss—resulted in an upsurge of environmental labels on goods. Environmental labels play a crucial role in assisting consumers in selecting environmentally superior products, fostering market development towards eco-friendly production systems, and serving as a foundation for product differentiation and increased product value. Despite a growing public interest in environmental quality and climate change, surveys reveal a gap between consumers’ environmental attitudes and actual purchasing behaviour. In addition, concerns about the complexity and cost of certification systems have arisen, with fears of creating market barriers for small producers. This review aims to provide an overview of environmental labelling in the context of animal food products, emphasising social and regulatory aspects, exploring technical considerations of life cycle thinking approaches in certification schemes, and discussing the pros and cons of standardising procedures for the development of multi-dimensional environmental labelling in the animal food sector.